Genomes of Leishmania parasites directly sequenced from patients with visceral leishmaniasis in the Indian subcontinent. - Malgorzata A Domagalska; Hideo Imamura; Mandy Sanders; Frederik Van den Broeck; Narayan Raj Bhattarai; Manu Vanaerschot; Ilse Maes; Erika D'Haenens; Keshav Rai; Suman Rijal; Matthew Berriman; James A Cotton; et al. (Public Library of Science (PLoS), 2019)
Whole genome sequencing (WGS) is increasingly used for molecular diagnosis and epidemiology of infectious diseases. Current Leishmania genomic studies rely on DNA extracted from cultured parasites, which might introduce sampling and biological biases into the subsequent analyses. Up to now, direct analysis of Leishmania genome in clinical samples is hampered by high levels of human DNA and large variation in parasite load in clinical samples. Here, we present a method, based on target enrichment of Leishmania donovani DNA with Agilent SureSelect technology, that allows the analysis of Leishmania genomes directly in clinical samples. We validated our protocol with a set of artificially mixed samples, followed by the analysis of 63 clinical samples (bone marrow or spleen aspirates) from visceral leishmaniasis patients in Nepal. We were able to identify genotypes using a set of diagnostic SNPs in almost all of these samples (97%) and access comprehensive genome-wide information in most (83%). This allowed us to perform phylogenomic analysis, assess chromosome copy number and identify large copy number variants (CNVs). Pairwise comparisons between the parasite genomes in clinical samples and derived in vitro cultured promastigotes showed a lower aneuploidy in amastigotes as well as genomic differences, suggesting polyclonal infections in patients. Altogether our results underline the need for sequencing parasite genomes directly in the host samples.